History, Typology, and Implementation of Islamic Law in Indonesia: Combination of Sharia and Fiqh or the Result of Historical Evolution? - Afridawati, Afridawati (Al-Risalah, 2021)
This paper highlights the history, typology, and implementation of Islamic law in Indonesia as well as proves that the law is a translation of both sharia and fiqh, rather than a historical evolution, as claimed by Ignaz Goldziher (1850 - 1921 AD) and some of his Muslim followers; nor does the law separate elements of ritual, muamalah, and politics as argued by Christian Snouck Hurgronje (1857–1936 AD), a stance that has deformalized Islamic law in Indonesia considering it an inferior legal institution. Focusing on Islamic civil law which is extracted from relevant literature sources, this paper shows that, to some extent, the influence of orientalists’ views is manifested, for example, in the books of Interfaith Jurisprudence and the Counter Legal Draft of Islamic Law Compilation (CLD - KHI) which have ample of "historical evolution" claims. In fact, the history, typology, and implementation of Islamic law in Indonesia have so far not only been for the benefit in the world but also in the hereafter. Thus, reforming Islamic civil law in line with the West’s human rights values, as done by CLD-KHI initiators, whom are greatly influenced by Ignaz Goldziher’s and Muhammad Anna'im’s "evolution of history", is like considering Islamic law limited to law for the world only, without any ukhrawi values.